Circadian Regulation of Immunity Through Epigenetic Mechanisms - Orozco-Solis, Ricardo; Aguilar-Arnal, Lorena (Frontiers in Cellular and Infection Microbiology, 2020)
The circadian clock orchestrates daily rhythms in many physiological, behavioral and molecular processes, providing means to anticipate, and adapt to environmental changes. A specific role of the circadian clock is to coordinate functions of the immune system both at steady-state and in response to infectious threats. Hence, time-of-day dependent variables are found in the physiology of immune cells, host-parasite interactions, inflammatory processes, or adaptive immune responses. Interestingly, the molecular clock coordinates transcriptional-translational feedback loops which orchestrate daily oscillations in expression of many genes involved in cellular functions. This clock function is assisted by tightly controlled transitions in the chromatin fiber involving epigenetic mechanisms which determine how a when transcriptional oscillations occur. Immune cells are no exception, as they also present a functional clock dictating transcriptional rhythms. Hereby, the molecular clock and the chromatin regulators controlling rhythmicity represent a unique scaffold mediating the crosstalk between the circadian and the immune systems. Certain epigenetic regulators are shared between both systems and uncovering them and characterizing their dynamics can provide clues to design effective chronotherapeutic strategies for modulation of the immune system.